User-generated content as a driver of brand value: Insights from web-based marketplaces - Li, Xin-Zhu; Kang, Xin (The Design journal, 2025)
This study investigates the impact of user-generated content (UGC) on brand value in web-based marketplaces, focusing on platforms like Threadless. UGC marketplaces enable designers to share their work with international audiences, reducing costs associated with printing, distribution, and advertising. Using theories of UGC, user-generated branding (UGB), and customer-based brand equity (CBBE), this study examines the role of UGC in fostering brand loyalty, purchase intention, and brand experience. The results demonstrate that UGC involvement has a positive effect on purchase intention, brand experience, and brand loyalty. Additionally, self-concept has a positive effect on brand loyalty. Brand loyalty is the most important aspect of CBBE assessment. The findings highlight the significance of UGC in shaping brand equity.